Cytogenetic and morphologic approaches of hybrids from experimental crosses between Triatoma lenti Sherlock & Serafim, 1967 and T. sherlocki Papa et al., 2002 (Hemiptera: Reduviidae) - Mendonca, Vagner Jose [UNESP]; Chaboli Alevi, Kaio Cesar [UNESP]; Oliveira Medeiros, Livia Maria de [UNESP]; Nascimento, Juliana Damieli; Vilela de Azeredo-Oliveira, Maria Tercilia [UNESP]; Rosa, João Aristeu da [UNESP] (Elsevier B.V., 2014)
The reproductive capacity between Triatoma lenti and Triatoma sherlocki was observed in order to verify the fertility and viability of the offspring. Cytogenetic, morphological and morphometric approaches were used to analyze the differences that were inherited. Experimental crosses were performed in both directions. The fertility rate of the eggs in crosses involving T. sherlocki females was 65% and 90% in F1 and F2 offspring, respectively. In reciprocal crosses, it was 7% and 25% in F1 and F2 offspring, respectively. The cytogenetic analyses of the male meiotic process of the hybrids were performed using lacto-acetic orcein, C-banding and Feulgen techniques. The male F1 offspring presented normal chromosome behavior, a finding that was similar to those reported in parental species. However, cytogenetic analysis of F2 offspring showed errors in chromosome pairing. This post-zygotic isolation, which prevents hybrids in nature, may represent the collapse of the hybrid. This phenomenon is due to a genetic dysregulation that occurs in the chromosomes of F1. The results were similar in the hybrids from both crosses. Morphological features, such as color and size of connexive and the presence of red-orange rings on the femora, were similar to T. sherlocki, while wins size was similar to T. lenti in F1 offspring. The eggshells showed characteristics that were similar to species of origin, whereas the median process of the pygophore resulted in intermediate characteristics in the F1 and a segregating pattern in F2 offspring. Geometric morphometric techniques used on the wings showed that both F1 and F2 offspring were similar to T. lenti. These studies on the reproductive capacity between T. lenti and T. sherlocki confirm that both species are evolutionarily closed; hence, they are included in the brasiliensis subcomplex. The extremely reduced fertility observed in the F2 hybrids confirmed the specific status of the species that were analyzed. (C) 2014 The Authors. Published by Elsevier B. V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/3.0/).
Keywords: Triatoma sherlocki; Triatoma lenti; Experimental crosses; Morphology; Cytogenetics